Islamic Law Review Of Wage Payment Practices At PT. Pundi Agro Makmur, Subah District - Eko Pujianto Hakim; Tehedi; Nilhakim (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2024)
This study discusses wage payment practices at PT. Pundi Agro Makmur, Subah District, focusing on two payment methods: bank transfer and cash payment. This study uses a qualitative approach with field research methods and an empirical sociological approach, collecting data through observation, interviews, and documentation. The results of the study indicate that wage payments via bank transfer are more efficient and there are no deductions, because the company only needs to provide wage recipient data and employee account numbers. In contrast, cash payments require rounding or deductions due to the difficulty in obtaining denominations below Rp. 1,000. However, the company does not provide information to employees regarding the deductions, and the results of the deductions are returned to the company through the KTU. From an Islamic law perspective, wage payments via bank transfer are permitted because they do not violate sharia. However, cash payments involving deductions without notification to employees are considered inconsistent with Islamic law. In conclusion, wage payment practices at PT. Pundi Agro Makmur need adjustments, especially in the cash payment method to comply with the principles of Islamic law.